The dialectics of ecology: Socialism and nature - Foster, John Bellamy (Delhi Aakar Books, 2025)
The Dialectics of Ecology is grounded in the contention that we are now faced with a concrete choice between ecological socialism and capitalist exterminism, and rooted in insights drawn from the classical historical materialist tradition. In this latest work, Foster explores the complex theoretical debates that have arisen historically with respect to the dialectics of nature and society. He then goes on to examine the current contradictions associated with the confrontation between capitalist extractivism and the financialization of nature, on the one hand, and the radical challenges to these represented by emergent visions of ecological civilization and planned degrowth, on the other.